ANALISA PENGUJIAN KEKERASAN MATERIAL BAJA KARBONRENDAH DAN BESI MENGGUNAKAN METODE UJI BRINNEL - Junaidi Junaidi; Ade Irawan (JITEKH, 2019)
Steel is iron with a carbon content of less than 2%. Steel can be formed into various shapes according to needs. Broadly speaking there are 2 types of steel, namely carbon steel and alloy steel. Carbon steel is divided into low carbon steel, medium carbon steel and high carbon steel. The classification of steel is significantly influenced by composition, structure and use. ST 37 iron is classified as low carbon steel, which has less carbon content according to specifications of 0.16%. This steel is also often used for machine constructions that rub against each other such as gears, shafts. Steel has mechanical properties, one of which is hardness. To determine the hardness value, the brinnel test method, the Vickers method and the Rockwell method are used. In this study, the brinnel method will be used, where the materials to be tested are low carbon steel and iron. This test can see the material hardness value of low carbon steel and iron so that it can be applied according to its function.